PEMANFAATAN MODUL GSM DAN MODUL GPS PADA SISTEM KEAMANAN SEPEDA MOTOR MENGGUNAKAN SMARTPHONE BERBASIS ARDUINO UNO - Yuda Irawan; Areta Sonya Rahajeng; Muhardi -; Refni Wahyuni (Universitas Islam Kuantan Singingi, 2020)
To facilitate control of lights in a home with a remote control so they invented a system of utilization of GSM Module Based Arduino Uno For Home Lighting Remote Control. The whole tool is divided into several parts, which consist of a Mobile, GSM SIM 800L module, arduino uno microcontroller, relay module, and lights. This tool works when Mobile sends an SMS (Short Message Service) containing commands to GSM SIM 800L, from GSM SIM 800L then to the microcontroller to process commands, from the microcontroller then to the relay module that works as a substitute for a switch that functions to turn on or turn off the lights which are desired.